PEMENUHAN HAK-HAK ATAS KESELAMATAN KERJA TERHADAP PEKERJA BATU KAPUR DI CV. BUKIT RAYA LAENDRYS KECAMATAN KAMANG MAGEK KABUPATEN AGAM - Iga S. Syahri; Firdaus Firdaus; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
In Law No. 13 Year 2003 on Employment contained in article 86 paragraph (1) it is mentioned that every worker/worker has the right to obtain protection for occupational safety and health, morals and decency, and appropriate treatment with human dignity and dignity as well as religious values. It is mandatory for employers to use Personal Protective Equipment (PPE) to avoid the risk of work accidents that may occur anywhere, and anytime, given that CV. Bukit Raya Laendrys is engaged in limestone production. However, in reality that happens CV. Bukit Raya Laendrys conducted by the company does not comply with the provisions of the prevailing laws and regulations. From that background can be formulated the following problems, namely: how to fulfillment the rights of work safety to limestone workers in CV. Bukit Raya Laendrys Kamang Magek District Agam Regency and how efforts should be made by CV. Bukit Raya Laendrys against workers who have had work accidents.This research is a sociological juridical study, the population of workers / production workers consisting of 3 people and the sample of 3 workers / laborers of the production part, because this study uses purposive sampling method. The data sources in this study are primary, secondary, and tertiary data. The data collection tools used are observation, interviews, documentation, and library studies. The analysis performed is qualitative descriptive analysis.Based on the results of this study, the authors concluded that in fulfilling the rights to work safety that should be received by workers in the form of Personal Protective Equipment that is not provided by CV. Bukit Raya Laendrys, and this violates the provisions of Law No. 13, 2003 on Employment in article 86 paragraph (1). Then efforts can be made by counseling about the importance of using PPE for workers/workers, providing adequate K3 facilities, and providing social security in the form of BPJS to workers who have an accident at work while working.Keywords : work safety, fulfillment of rights, work accident